2021
DOI: 10.2217/fon-2020-1225
|View full text |Cite
|
Sign up to set email alerts
|

Ixazomib-Lenalidomide-Dexamethasone in Routine Clinical Practice: Effectiveness in Relapsed/refractory Multiple Myeloma

Abstract: Aim: To evaluate the effectiveness and safety of ixazomib-lenalidomide-dexamethasone (IRd) in relapsed/refractory multiple myeloma in routine clinical practice. Patients & methods: Patient-level data from the global, observational INSIGHT MM and the Czech Registry of Monoclonal Gammopathies were integrated and analyzed. Results: At data cut-off, 263 patients from 13 countries were included. Median time from diagnosis to start of IRd was 35.8 months; median duration of follow-up was 14.8 months. Overall res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…However, a significant OS benefit was not observed in the final analysis, possibly due to the type of subsequent lines of therapies including an inferior proportion of patients in the IRd group who received daratumumab‐based compared with the Rd group 43 . Real‐world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results 44–47 . Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all‐oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM 48,49 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a significant OS benefit was not observed in the final analysis, possibly due to the type of subsequent lines of therapies including an inferior proportion of patients in the IRd group who received daratumumab‐based compared with the Rd group 43 . Real‐world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results 44–47 . Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all‐oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM 48,49 …”
Section: Discussionmentioning
confidence: 88%
“…43 Real-world studies have confirmed the effectiveness and safety of IRd in the routine clinical practice in accordance with the clinical trial results. [44][45][46][47] Interestingly, pharmacoeconomic analyses both in the United States of America and in Europe have suggested that all-oral IRd regimen is among the least expensive approved triplet regimens for patients with RRMM. 48,49 The combination of Dara-Ixa-dex has been also evaluated in the first-line treatment of patients with NDMM who are not fit for ASCT.…”
mentioning
confidence: 99%
“…In the routine clinical practice, the all‐oral route of administration and the favorable safety profile make this regimen potentially suitable for the treatment of elderly pts with comorbidities and/or impaired PS 5,6 . Several observational studies have indeed reported a higher prevalence of older age, impaired PS, advanced stage disease, >2 pLoT in the real‐world population treated with IRd, showing comparable effectiveness with OR rates ranging from 60% to 74% and mPFS ranging from 11.4 to 43 m 7–15 . Moreover, a significant proportion of pts (17%–39%) in the real‐world setting has previous exposure to Len compared to only 12% in the MM1 study.…”
Section: Discussionmentioning
confidence: 99%
“…In the routine clinical practice, the all-oral route of administration and the favorable safety profile make this regimen potentially suitable for the treatment of elderly, frail patients (pts) [2][3][4] who are under-represented in the clinical studies. 5,6 Several observational studies [7][8][9][10][11][12][13][14][15] of IRd have confirmed the effectiveness of IRd with ORR ranging from 60% to 74% and mPFS from 11.4 to 27.6 m in real-world setting, despite a higher prevalence of elderly and heavily pre-treated pts, compromised performance status (PS), and advanced stage disease. A proportion of pts ranging from 17% to 38% in the published real-world studies had previous exposure to lenalidomide (Len) compared with only 12% in the MM1 study.…”
Section: Introductionmentioning
confidence: 99%
“…Several RWE worldwide supported the benefit of ixazomib-based treatment in RRMM patients regarding PFS [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. None of these studies compared IRD vs. RD but the outcomes were quite similar with median PFS varying from 17–31 months.…”
Section: Discussionmentioning
confidence: 99%